Relationship between social physique anxiety, body image dissatisfaction, personality types and self-esteem among Malaysian young adults - Jaapar, Nur Syamira; Ma’rof, Aini Azeqa; Abdullah, Haslinda (Human Resource Management Academic Research Society, 2024)
This study examines the relationship between social physique anxiety, body image dissatisfaction, personality traits (extraversion and neuroticism), and self-esteem among Malaysian young adults. Using a sample of 400 participants, the research investigates how these factors interact to influence self-esteem levels, with a focus on the psychological impact of body image concerns and personality characteristics. Quantitative methods, including correlation and regression analyses, were employed to assess the relationships between these variables. The findings reveal that social physique anxiety, body image dissatisfaction, and neuroticism are significant negative predictors of self-esteem, while extraversion positively contributes to self-esteem. Social physique anxiety and body image dissatisfaction had a particularly strong negative impact, suggesting that individuals who experience anxiety about how others perceive their bodies tend to have lower self-esteem. These results highlight the need for interventions aimed at reducing body image concerns and supporting emotional stability to improve self-esteem among young adults. The study offers valuable insights into the factors that shape self-esteem in this population and provides practical implications for mental health programs targeting body image and personality-related challenges.